FGFR3 Mutation Status and FGFR3 Expression in a Large Bladder Cancer Cohort Treated by Radical Cystectomy: Implications for Anti-FGFR3 Treatment? - van Rhijn, Bas W.G.; Mertens, Laura S.; Mayr, Roman; Bostrom, Peter J.; Real, Francisco X.; Zwarthoff, Ellen C.; Boormans, Joost L.; Abas, Cheno; van Leenders, Geert J.L.H.; Götz, Stefanie; Hippe, Katrin; Bertz, Simone; et al. (European Urology, 2020)
Oncogenic fibroblast growth factor receptor 3 (FGFR3) mutations were associated with favorable bladder cancer in a series of 1000 radical cystectomy cases. Moreover, patients with FGFR3 mutant tumors would be more likely to benefit from anti-FGFR3 therapy than patients with overexpression only.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Bladder; Cancer; Cystectomy; Expression; FGFR3; Mutation; Urothelial carcinoma